RHETORIC AS AN IMPORTANT TOOL IN LEGAL DISCOURSE - Ayvazyan, Anna (Foreign Languages for Special Purposes, 2024)
The present article aims at highlighting the interrelationship between language, law and rhetoric, showing the extent to which language use influences legal discourse.Rhetoric is the art of persuasive speaking, a very vital element in the realm of law. It is an important tool in jurisprudence to present actions and evidence that helps to persuade the court to achieve the desired result. That art of persuasion is due to the circumstance of speaking wisely and intelligently.Thus, it is noteworthy to emphasize that the rhetorical use of language can be applied in the courtroom through the use of various strategic tricks that aim to achieve persuasion and/or manipulation.
Keywords: rhetoric; persuasive speech; art of speech; domain of law; language strategies